2020
DOI: 10.1182/blood-2020-140339
|View full text |Cite
|
Sign up to set email alerts
|

Phase 3 Study of Lenalidomide (LEN) Vs Placebo in Non-Transfusion Dependent (TD) Low Risk Del(5q) MDS Patients - Interim Analysis of the European Sintra-REV Trial

Abstract: Background: Most IPSS low and int1 (lower) risk MDS patients with isolated del(5q) develop RBC TD or need treatment for symptomatic anemia early after diagnosis (median time to transfusion/treatment of 20 months, López Cadenas et al abstract 3180 ASH, 2016). Lenalidomide (LEN) is a reference treatment in MDS-del(5q) but approved in many countries only when RBC-TD occurs. LEN directly targets the del(5q) clone improving anemia and quality of life. Limited data also suggest a role of LEN in non-TD patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The median duration of dose reduction or interruption were (p = .022), and these events were not related to the drug. 69 In Table 3 data of studies regarding lenalidomide use in del(5q) MDS patients are summarized.…”
Section: 41 | Esasmentioning
confidence: 99%
See 1 more Smart Citation
“…The median duration of dose reduction or interruption were (p = .022), and these events were not related to the drug. 69 In Table 3 data of studies regarding lenalidomide use in del(5q) MDS patients are summarized.…”
Section: 41 | Esasmentioning
confidence: 99%
“…Hematological toxicity occurred more frequently in lenalidomide arm compared to the placebo arm, with 40 and 4 patients affected, respectively. At least one SAE was observed in 31.6% of the lenalidomide patients compared to 4.8% in the placebo arm ( p = .022), and these events were not related to the drug 69 . In Table 3 data of studies regarding lenalidomide use in del(5q) MDS patients are summarized.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, therapies such as lenalidomide have been reserved for transfusion-dependent patients; however, there are ongoing investigations exploring the possible benefits of starting treatments prior to transfusion dependence. An interim analysis of the phase 3 European Sintra-REV trial comparing lenalidomide to placebo in patients with non-transfusion-dependent del(5q) LR-MDS [ 52 ] showed that the patients receiving lenalidomide had a significantly longer time to transfusion dependence compared with patients receiving placebo (76 vs. 26 months; P = 0.021) [ 52 ]. However, a comparison to ESA would have been more in line with the current European guidelines.…”
Section: The General Approach To the Management Of Patients With Lr-mdsmentioning
confidence: 99%
“…Whether this practice will alter the natural course of the disease and has an impact on long‐term outcome is not known, as is the optimal time of starting therapy. However, interim analyses of the SINTRA‐REV trial (ClinicalTrials.gov Identifier: NCT01243476) in non‐TD LR MDS del(5q) patients suggest that early treatment with lenalidomide at low doses (5 mg) prolongs the time to and decreases the risk of TD with cytogenetic responses 7 . This is supported by our data—although not corrected for disease duration and risk stratification—as patients with no RBC transfusions during the first cycle of treatment with lenalidomide had a significant improvement of median OS ( P = 0.014).…”
Section: Figurementioning
confidence: 99%